Actores públicos y privados de la fiscalidad minera española en el siglo xix - Gérard Chastagnaret (Mélanges de la Casa de Velázquez, 2016)
For several decades after 1868 the Spanish tax on mining introduced by Fausto Elhuyar’s decree of 1825 all but disappeared through pressure from an ultra-liberal state apparatus, just as the country embarked on large-scale mining controlled by large enterprises. The influence of these enterprises in the drafting of taxation only became clear in the latter decades of 19th century when the state tried to raise the tax burden on what was the prime export sector in the national economy. The mining lobbies sought to mitigate the impact of the Villaverde reforms, which in any case came at a time when most coalfields were beginning to show clear signs of exhaustion. Thus it is the public authorities which were primarily responsible for the failure to apply fiscal pressure when mining was growing and at its height; the mining companies merely sought to attenuate the impact of changes when these could not be avoided.